Pengaruh Kepemimpinan Dan Kompetensi Terhadap Kinerja Karyawan (Studi Kasus Pada PT. Sukses Mitra Sejahtera) - Gandung Satriyono; Meme Rukmini (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to determine the effect of leadership and competence on employee performance at PT. Success Partners Prosperous. Case studies were conducted on all employees of the HRD and GA division at PT. Success Partners Prosperous. This data was obtained through direct distribution of questionnaires. The samples studied in this study were 46 respondents using saturated sampling techniques or taking all members of the population to conduct research. The data analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that: (1) Leadership (X1) on Employee Performance (Y) has a partial effect with a coefficient value of 4.411 with a significant level of 0.000. (2) Competence (X2) has no significant effect on Employee Performance (Y) with a coefficient value of 0.932 with a significant level of 0.356. (3) Leadership (X1) and Competence (X2) on Employee Performance (Y) have a simultaneous effect with a coefficient value of 9.769 with a significant level of 0.000. Keywords: Leadership, Competence, Employee Performance